Design and analysis of multi pass flow in shell-and-tube heat exchange - Lee, Chuan Xiang
The aim of this final year project is to expose university undergraduates to the world of HVAC (Heating, Ventilating, and Air-Conditional) which are widely use in industry and undergraduate students need to perform design and analysis of one shell pass two tube passes shell and tube heat exchanger.